AKSARA CARD BERBASIS TEKNOLOGI AUGMENTED REALITY SEBAGAI INOVASI PEMBELAJARAN AKSARA JAWA PADA ANAK SEKOLAH DASAR - Afenia Wulan Cahya; Lisa Kusuma Aprilia; Ana Fauziyah; Nur Laili Rahmawati; Daning Hentasmaka (Cahaya Ilmu Bangsa Institute, 2024)
Learning Media Plays a Vital Role in Creating an Interactive and Enjoyable Learning Environment. In today’s educational landscape, with the advancement of technology penetrating the field of education, it’s unfortunate that teachers still struggle at times to determine effective media that can engage students’ interest and attention. This challenge becomes even more pronounced when teaching subjects with limited popularity, such as regional languages, particularly Javanese. Research by Nurhasanah et al. (2016) revealed that 60% of 40 elementary school students were unable to read Javanese script. This issue arises due to low interest in learning and the monotonous use of traditional teaching materials, primarily textbooks and modules. These constraints highlight the inadequacy of existing learning media in capturing students’ attention and providing an enjoyable and interactive learning experience. Addressing this phenomenon, researchers have developed the “Aksara Card Based on Augmented Reality Technology” as an innovative solution for Javanese script learning. The research employed the Research and Development (R&D) method, which involves developing specific products and evaluating their effectiveness. The development process occurred iteratively, with each step building upon the insights gained from the previous stages. The results include the creation of Aksara Cards and an analysis of sales data. In June, 16 pieces of the product were sold, while in July, sales surged to 30 pieces—an impressive 75% increase from the predefined target. Overall, the revenue generated from Aksara Card sales during that period amounted to Rp331,500. The sales graph reflects positive performance and promising growth potential for the upcoming months